The Educational System as a Monument of Functionalism in Educational Discourse - Danuta Uryga (University of Lower Silesia, 2014)
The theme of the article is the concept of the educational system-its origin and relationship with a specific strand of scientific thought, which is functionalism. "The education system," the key term for education in Poland, is saturated with content that less and less corresponds to the needs and expectations of society. The author carries out an analysis of the content, referring to some currents of pedagogical thought and pointing at the traps in the educational discourse, dangerous to its thoughtless participants.